1994
DOI: 10.2508/chikusan.65.525
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fasting on the Adipose Tissue Weight in Chicks, with Reference to Changes in Triglyceride Synthesis and Fatty Acid Oxidation

Abstract: Triglyceride synthesis and fatty acid oxidation in the chick adipose tissue were studied by measuring the incorporation of [1-14C] acetate or [1-14C] palmitate into triglycerides

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The results of Hasegawa et al (1994a) indicated that the LPL activity of chicks decreased during fasting. Also, Gasquet and Pequignot (1972) noted that LPL activity decreased in mouse adipose tissue during fasting.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The results of Hasegawa et al (1994a) indicated that the LPL activity of chicks decreased during fasting. Also, Gasquet and Pequignot (1972) noted that LPL activity decreased in mouse adipose tissue during fasting.…”
Section: Discussionmentioning
confidence: 94%
“…Previous investigations have indicated that fasting decreases the lipogenesis capacity and increases the lipolysis rate of chickens (Calabotta et al, 1985;Goldman et al, 1985;Hasegawa et al, 1994b;Leveille et al, 1975). Other works noted increased activities of lipoprotein lipase (Hasegawa et al, 1994a) and hormone-sensitive lipase (Anthony et al, 1990) in fasting chickens. Also, the lipid metabolism of chickens in the laying period differs from that in the growing period (Walzem, 1996).…”
Section: Introductionmentioning
confidence: 98%